Modeling and simulation of inverter-controlled hybrid photovoltaic-wind connected to the grid generation system - Diblawe, Dahir Kheyre (2018)
The rapid growth demand for energy and the depletion of fossil fuels leads researchers to develop alternative and sustainable energies sources like wind and solar renewable sources which is becoming the largest potential in renewable energies. The aim of this project is to design I Ok W hybrid PY-Wind hybrid connected to the grid generation system, this system is regulated by the common DC link in order to contribute some power to the grid. The project consists of Permanent Magnet Synchronous (PMSG) as a wind generator, solar connected in series and parallel modules, DC-DC Boost converter equipped with MPPT, this, Maximum power point tracker (MPPT) control is essential to extract the maximum power of the output of photovoltaic power generation system and wind turbine at its maximum power point. Perturbation & observation (P&O) strategy is utilized and modelled in MATLAB/Simulink. This strategy is modest in operation and hardware requirement is minimal, a Phase Locked Loop (PLL) is used for control of multifunctional YSC. The voltage source converter (YSC) controller uses the load and source forward terms for fast dynamic response by regulating and giving required power to the grid. The simulation studies are performed on MATLAB/Simulink. The alternating power from the sources is connected voltage source inverter which regulates the injected DC voltages before sending to the grid. This inve11er transfers the energy drawn from the wind turbine and PY array to the grid by keeping common DC voltage in constant value. The simulation results demonstrates the control performance and dynamic behaviour of the hybrid PY-wind connected to the grid generation system by using MA TLAB/Simulink.